Birds of a Feather Feel Together: Emotional Ability Similarity in Consumer Interactions - Kidwell, Blair; Lopez-Kidwell, Virginie; Blocker, Christopher; Mas, Erick M (Journal of Consumer Research, 2020)
The authors introduce emotional ability similarity to explain consumer satisfaction in interactions with frontline sales and service employees and other consumers beyond the effects of traditional relational variables in the similarity–attraction paradigm. Four studies examine how and why similar abilities for using emotional information between two people promote relational success in marketplace exchanges. We find that, when interacting with others, consumers who exchange nonverbal information with their partners experience (dis)similarity in their emotional ability (EA). Similar dyads who rely on expressive (high–high EA pairs) or inexpressive (low–low EA pairs) emotion norms experience significantly greater satisfaction in their interactions than consumers with dissimilar norms (high–low EA pairs). Together, these findings advance the understanding of consumer relationships and satisfaction by establishing EA similarity as a new avenue for consumer research.